1994
DOI: 10.1007/bf01291165
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pre-saddle neutrons on the fission fragment angular distribution

Abstract: Abstract. In the present note it is shown that distinguishing between pre-saddle and saddle-to-scission neutrons removes a discrepancy previously found [2][3][4] between data for the fission fragment anisotropy and an analysis in the framework of the transition state theory in which it has been assumed that all pre-scission neutrons influence the temperature at the saddle point. The analysis of the present paper requires a fairly weak (fl = 2 * 1021s -1) friction at compact shapes, in agreement with a previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Different fission characteristics of the heavy compound nuclei 224 Th and 248 Cf produced, respectively, in the reactions 16 O + 208 Pb and 16 O + 232 Th have been intensively investigated experimentally [63][64][65][66][67][68][69][70][71][72][73][74][75][76] and theoretically [20,23,24,44,71,83]. The results of 3D Langevin calculations [23,24,44] demonstrated that a simultaneous reproduction of the width 064619-6 of fission fragment mass distribution and mean prescission neutron multiplicity for heavy fissioning nuclei is difficult.…”
Section: Cross Sections Parameters Of the Fission Fragment Med And mentioning
confidence: 99%
“…Different fission characteristics of the heavy compound nuclei 224 Th and 248 Cf produced, respectively, in the reactions 16 O + 208 Pb and 16 O + 232 Th have been intensively investigated experimentally [63][64][65][66][67][68][69][70][71][72][73][74][75][76] and theoretically [20,23,24,44,71,83]. The results of 3D Langevin calculations [23,24,44] demonstrated that a simultaneous reproduction of the width 064619-6 of fission fragment mass distribution and mean prescission neutron multiplicity for heavy fissioning nuclei is difficult.…”
Section: Cross Sections Parameters Of the Fission Fragment Med And mentioning
confidence: 99%
“…The one-dimensional Langevin equations was applied to explore the main features of angular distribution [66,67]. Recently Jia and Bao [30] published the results of the angular distribution calculations within two-dimensional Langevin dynamics.…”
Section: The Effect Of Model Dimension On the Angular Distributionmentioning
confidence: 99%
“…The one-dimensional Langevin equations was applied to explore the main features of angular distribution [204,205]. In 2007 Jia and Bao [206] have published the results of the angular distribution calculations within twodimensional Langevin dynamics.…”
Section: The Effect Of Model Dimension On the Angular Distributionmentioning
confidence: 99%